Accelerated sintering of high-performance oxide dispersion strengthened alloy at low temperature. (November 2021) - Dong, Zhi; Ma, Zongqing; Liu, Yongchang
Abstract: Powder metallurgy generally is a preferred method to consolidate and prepare some refractory metals considering their high melting temperatures. However, sintering such materials to high density while maintaining fine grain structure is challenging, and generally require ultrahigh temperature or need to be assisted by external pressure. Especially, the preparation of nanostructured oxide dispersion strengthened (ODS) refractory metals at low temperature is more difficult because grain coarsening and densification are simultaneously hindered by the common oxide addition. Thus, it is of great sense to explore a kind of oxide that can be used as both strengthening phase and sintering accelerator. In this work, after extensive theoretical calculation and experimental observation, it is found that the accelerated sintering at low temperature can be achieved in W-HfO2 system. In the absence of external pressure or activator, this system can be rapidly densified without undesirable grain coarsening at a relative low temperature of only 1480 ˚C. Through kinetic analysis and density functional theory (DFT) calculation, it was confirmed that the intergranular HfO2 particles provide a rapid diffusion transport pathway for W atoms in support of densification at temperature of interest. As a result, this alloy exhibits a homogeneous microstructure with ∼97% relative density and ∼200 nm grain size, which renders our alloy with an ultrahigh compressive strength of ∼3 GPa, much higher than the reported values. We believe that the accelerated sintering mechanism found in our W-HfO2 system can be applicable to other refractory metals to prepare high-density nanocrystalline alloys with excellent properties. Graphical abstract: Image, graphical abstract